THU0080 The Role of C5ORF30 in Rheumatoid Arthritis Pathogenesis. (23rd January 2014) - Davies, H.; Muthana, M.; Khetan, S.; Adeleke, G.; Hawtree, S.; Morrow, F.; Ciani, B.; Wilson, A. G.
Abstract : Background: A recent genome wide association study identified the variant rs26232 in the first exon of an uncharacterized gene C5orf30 as a rheumatoid arthritis susceptibility variant 1 . In addition, it has been associated with severity of radiological joint damage suggesting a role in tissue breakdown 2 . To date there is no function assigned for C5orf30 and neither the gene or protein coded show homology to any known functional sequences. However, C5orf30 is highly conserved in chimpanzee, dog, cow, mouse, chicken, and zebrafish (orthologs). Objectives: The aim of this study is to determine the biological roles of C5orf30 in rheumatoid arthritis. Methods: Real time PCR and western blotting were used to examine C5orf30 transcript and protein levels in fibroblast-like synovial cells (FLS stimulated with TNF & hypoxia) and peripheral blood leukocytes isolated from RA patients and healthy individuals. Immunohistochemistry on synovial samples was used to determine expression of C5orf30 including co-localisation using antibodies to macrophages (CD68), fibroblasts (5B5), T (CD3) & B (CD19) cells. To investigate gene function siRNA was used to knockdown C5orf30 in synovial FLS in vitro. Results: Expression of C5orf30 was detected at lower levels in peripheral blood leukocytes of RA patients compared to healthy controls (117 patients vs. 102 controls, p =0.00052). C5orf30 was expressed in FLS and was found to be up-regulated by hypoxia (8-fold) and down-regulated by TNF (0.5-fold). Confocal microscopy revealed C5orf30 to be strongly expressed in both the nuclear and cytoplasmic compartment of synovial lining cells including macrophages and fibroblasts, but not T & B cells. C5orf30 was undetectable in arthroscopy sections obtained from osteoarthritis or control synovium. Approximately 80% C5orf30 knockdown has been achieved by siRNA, and preliminary studies have shown C5orf30 knockdown increased FLS invasion into matrigel. Conclusions: C5orf30 is expressed in synovial cells but not in circulating peripheral blood leukocytes obtained from RA patients, implying that C5orf30 is expressed in a tissue-specific manner. C5orf30 knockdown increased FLS migration into matrigel suggesting C5orf30 is negatively regulating cellular invasion. Together this points to an anti-inflammatory role for C5orf30 in RA and this may be a promising target for novel therapeutic strategies. References: Stahl EA, Raychaudhuri S, Remmers EF, et al. Genome-wide association study meta-analysis identifies seven new rheumatoid arthritis risk loci. Nat Genet 2010;42:508-14. Wilson AG, Teare M, van der Helm-van AH, Moore D, Knevel R, Kleszcz A, Huizinga T (2011). Identification and validation of a novel marker for radiological severity in RA. Abstract N° OP0229. EULAR Disclosure of Interest: None Declared